Peran GCG dalam Memoderasi Hubungan Modal Intelektual, CSR, dan Kinerja Perusahaan - Yopie, Santi; Ilu, Jennifer (E-Jurnal Akuntansi; Vol 33 No 9 (2023)DO - 10.24843/EJA.2023.v33.i09.p11, 2023)
The occurrence of economic integration and technological progress has caused globalization to make business competitiveness increasingly tight. The level of business competition depends on investment from investors who are able to influence increased company performance. The research was conducted to examine the influence of intellectual capital and CSR on company performance and analyze the impact moderated by GCG. Sample selection was carried out using a purposive sampling technique resulting in 33 companies with a data period of 4 years, totaling 129 data. Data testing was carried out using multiple linear analysis. The research results show that intellectual capital, CSR, and GCG do not affect company performance. GCG is able to strengthen the relationship between intellectual capital and company performance and strengthen the relationship between CSR and company performance. Keywords: Intellectual Capital; CSR; GCG; Company Performance